2004
DOI: 10.1124/jpet.104.067330
|View full text |Cite
|
Sign up to set email alerts
|

Strong Protein Adduct Trapping Accompanies Abolition of Acrolein-Mediated Hepatotoxicity by Hydralazine in Mice

Abstract: Acrolein is a highly reactive ␣,␤-unsaturated aldehyde that readily alkylates nucleophilic centers in cell macromolecules. Typically, such reactions proceed via Michael addition chemistry, forming adducts that retain an electrophilic carbonyl group. Since these species participate in secondary deleterious reactions, we hypothesize that inactivation of carbonyl adducts may attenuate acrolein toxicity. Indeed, we recently established that the nucleophilic antihypertensive drug hydralazine readily "traps" acrolei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 37 publications
2
75
0
Order By: Relevance
“…We identified the antihypertensive hydralazine, among the strongest nucleophiles in clinical use, as a powerful inhibitor of acrolein toxicity (Lalich and Paik, 1975;Burcham et al, 2002). Although its protective efficacy seemed to be related to its acrolein-scavenging properties in cell-free systems (Kaminskas et al, 2004b), we found that hydralazine also reacts extensively with adducts formed during protein modification by acrolein (Burcham et al, 2004;Kaminskas et al, 2004b). The present work breaks new ground by establishing that the latter adduct-trapping reactivity is more closely related to hydralazine cytoprotection than the direct acrolein-scavenging reaction (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified the antihypertensive hydralazine, among the strongest nucleophiles in clinical use, as a powerful inhibitor of acrolein toxicity (Lalich and Paik, 1975;Burcham et al, 2002). Although its protective efficacy seemed to be related to its acrolein-scavenging properties in cell-free systems (Kaminskas et al, 2004b), we found that hydralazine also reacts extensively with adducts formed during protein modification by acrolein (Burcham et al, 2004;Kaminskas et al, 2004b). The present work breaks new ground by establishing that the latter adduct-trapping reactivity is more closely related to hydralazine cytoprotection than the direct acrolein-scavenging reaction (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Using rabbit antiserum against drug-labeled adducts, we also detected strong adduct-trapping in a wide range of cell proteins from mouse hepatocytes treated briefly with allyl alcohol and cytoprotective concentrations of hydralazine (e.g., 2 to 50 M; see Burcham et al, 2004). Moreover, intense protein adducttrapping occurred in the livers of allyl alcohol-intoxicated mice that received hepatoprotective doses of hydralazine (Kaminskas et al, 2004b).…”
mentioning
confidence: 93%
“…The reaction was started by adding 15 mL of 10 mmol/L NADPH. AR activity was measured at 340 nm at 25 C for 5 min.…”
Section: Ar Assaymentioning
confidence: 99%
“…24 Acrolein can cause hepatotoxicity in vitro and in vivo. [25][26][27][28] However, the mechanisms involved in acrolein-induced hepatocellular toxicity are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Low hydralazine concentrations also block the toxicity of acrolein in diverse cell types including hepatocytes, neuronal cells, and lung epithelial cells (LiuSnyder et al, 2006;Burcham et al, 2007;Truong et al, 2009). Protective efficacy for hydralazine has also been shown in several animal models of carbonyl-mediated pathology, including diabetic nephropathy, allyl alcohol hepatotoxicity, spinal cord injury, atherosclerosis, and experimental autoimmune disease (Nangaku et al, 2003;Kaminskas et al, 2004b;Vindis et al, 2006;Hamann et al, 2008;Leung et al, 2011). The mechanism(s) underlying drug efficacy in these models is unclear because the direct reactivity of hydralazine with electrophilic carbonyls may be constrained within biological systems.…”
Section: Introductionmentioning
confidence: 99%